SOURCES OF NITROGEN AND MODES OF APPLICATION IN MAIZE UNDER NO TILLAGE CROP - Kaneko, F. H.; Arf, O.; Sabundjian, M. T.; Ferreira, J. P.; Gitti, D.C.; Leal, A.J.F.; Nascimento, V. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Maize is one of the most demanding cultures fertilizers, especially nitrogen. Thus this study aimed to evaluate, in cerrado soil, the effect of N sources and application methods with and without merger by irrigation water, in maize in no-till system. The experiment was conducted in red Latosol. The experimental design was randomized blocks with 12 treatments in a factorial 3x2x2, with four replications. Treatments consisted of two N sources (urea, ammonium nitrate and witness - without N), two application methods (broadcasted and banded) with or without incorporating with blade irrigation of 10 mm. were evaluated: the mass of one hundred grains and grain yield (kg ha-1). It can be concluded that there was effect of nitrogen fertilization, and ammonium nitrate provided the highest grain yield. Regarding the picture modes when N fertilizer was applied to haul obtained the highest grain yield. Since the incorporation of the N irrigation with 10 mm blade, but it influenced the mass of grains, not increased the grain yield.